In situ measurements reveal extremely low pH in soil. (December 2017) - Nielsen, Knud Erik; Irizar, Amaia; Nielsen, Lars Peter; Kristiansen, Søren M.; Damgaard, Christian; Holmstrup, Martin; Petersen, Asger R.; Strandberg, Morten
Abstract: We measured pH in situ in the top organic soil horizons in heathland and pine forest and found values between 2.6 and 3.2. This was 0.5–0.8 units lower than concurrent laboratory pH measurements of the same soil, which raises questions about the interpretation of pH measurements. We propose that the higher pH recorded by standard laboratory methods may be due to buffering ions from soil biota released from drying, grinding and rewetting of soil samples, whereas the in situ pH reflects the correct level of acidification. Highlights: Robust field electrodes ensures true in situ pH measurements. The majority of data were more acid than expected with pH between 2.6 and 3.1. Deviation up to 1 pH unit between in situ and standard pH of the soil sample. In situ pH is within the range of the iron buffer with no visual toxic effect on biota. Do living and dead soil biota in the sample contribute to increase pH?